Relationship between repeated sprint speed and sprint speed degradation to maximal aerobic capacity in collegiate male soccer players - Ryan, G.; Eisenman, M.; DeJohn, D.; Phillips, S. (The Journal of Strength and Conditioning Research, 2021)
Soccer requires significant contribution of both the aerobic and anaerobic energy systems. Coaches and technical staffs use a variety of field tests to estimate maximal aerobic capacity (VO2max) as well as maximum sprint speed (Smax) to determine fitness of players prior to the season. While there are benefits to field tests, such as the 12-minute Cooper Test (CT) to estimate VO2max, there are a number of limitations, including time and motivation, which may impact values obtained via these tests. Due to the vigorous and intermittent demands of the sport, repeated sprint performance and speed degradation (SD) may be a more sport-specific, and useful, predictor of VO2max in sports like soccer. Purpose: To examine the relationship between Smax and SD during 3 repeated 30 × 15 yard sprints to estimated VO2max in collegiate male soccer players. Methods: 17 Division I male soccer players wore a GPS bioharness and underwent the CT and 3, 30 × 15 yard repeated sprints as a team, separated by a week, as part of their conditioning program. The CT was completed using established protocol. For the 30 × 15 repeated sprints, players sprinted maximally for 30 yards, touched a line, and immediately sprinted back for 15 yards, then walked the remaining 15 yards to the initial starting point. Upon reaching the starting line, players repeated the sprint in the same manner 2 more times. Smax for each 30 (Smax30-1,2,3) and 15 yard (Smax15-1,2,3) sprint, as well as SD (difference in Smax from Smax30-1 to Smax30-3 and Smax15-1 to Smax15-3) were recorded in miles per hour from the GPS software after testing. Pearson correlations were run to evaluate the relationship between VO2max and all Smax and SD variables. Additionally, a forward simple linear regression was calculated to predict VO2max based on all variables. Significance of correlations and prediction equations was set at p = 0.05. Results: A significant, moderate, positive correlation existed between VO2max and Smax30-2 (r (17) = 0.49, p = 0.05) and a significant, moderate, negative correlation existed between VO2max and S30D (r (17) = -0.50, p = 0.04). A significant regression equation was found (F (1,16) = 4.95, p = 0.04; R2 = 0.25). S30D was the only significant predictor of VO2max (VO2max = 65.197-4.260(S30D)). 95% CIs were (57.266-73.129) and (-8.343 to -0.178) respectively. Neither S15D nor any Smax values were significant contributors (p > 0.05). Conclusions: Players who maintained Smax (smaller SD) across sprints had higher VO2max compared to those with higher SD during the test. Only a modest relationship existed between Smax during any sprint (Smax30-2) and VO2max, indicating that the ability to maintain speed during 30 yard repeated sprints is a better predictor of aerobic performance than Smax. S30D shows promise as an estimator of VO2max in collegiate male soccer players. Practical Applications: The ability to maintain Smax is a major determining factor to increased aerobic capacity among soccer players. Strength and conditioning staffs may want to focus on repeated sprint performance in training to help match both aerobic and anaerobic demands of the sport. Lastly, due to the smaller time commitment of the 30 × 15 repeated sprints (~3 minutes) and increased specificity, coaches and technical staffs may want to consider S30D as a value for estimating VO2max in collegiate soccer players. However, more testing is needed before relying solely on this method for determining VO2max.